Endodontist's dilemma: Retreat or extract? - Girija Abhijeet Kolarkar; Vimala Nilker; Leena Padhye (Wolters Kluwer Medknow Publications, 2020)
The retreatment in endodontics, when correctly incorporated, permits the conservation of dental components. The removal of different substances from root canal such as gutta-percha, fractured endodontic instruments, and silver points is the remedy to a successful retreatment of teeth with failed primary endodontic treatment. It is often required to take out metal posts placed in the root canals in teeth showing great loss of the clinical crown. Their removal is of specific importance for evaluating endodontic space, cleaning, and disinfection of root canal. The intention of this case report is to introduce techniques and armamentarium for removing metal posts placed in the root canal of right maxillary second premolar with mutilated clinical crown requiring retreatment. This manner of intracanal metal post removal and retreatment is well recommended and successful since the teeth remained with good signs of prognosis after the treatment.